Edible insects in the metabolomics era. First steps towards the implementation of entometabolomics in food systems. (January 2022) - Poma, Giulia; Cuykx, Matthias; Da Silva, Katyeny Manuela; Iturrospe, Elias; van Nuijs, Alexander L.N.; van Huis, Arnold; Covaci, Adrian
Abstract: Background: Edible insects are a nutritious and sustainable alternative source of animal proteins, and consequently are nowadays promoted as human food and animal feed worldwide. Ensuring the quality, safety, and traceability of insect foods is thus critical to maintain a safe and economically sustainable supply chain. Providing a simultaneous analysis of a wide range of chemical compounds, metabolomics and non-target screening (NTS) have become important mass spectrometry-based tools in the field of food sciences. At this moment, however, the application of these analytical techniques to edible insect-related topics has been largely overlooked. Scope and approach: In this Commentary, we explore the potential of "entometabolomics" for food science and industry. We address the hurdles associated with safety, quality, and traceability of insects as food and feed and current issues related with insect industrial applications. Key findings and conclusions: Current applications of metabolomics and NTS in traditional food systems are presented. We propose ways to translate and implement such techniques for the edible insect sector. Even if the broad applicability of metabolomics and NTS approaches is still hampered by technical challenges, we show the high potential of entometabolomics when implemented into the insect food and feed industry and research. Highlights: Edible insects are a valuable source for human food and animal feed worldwide. Shifts in diet habits need to be accompanied by appropriate food control measures. Metabolomics is a reliable tool for safety, quality, traceability of insect foods. Entometabolomics addresses challenges related to insect industrial applications.